Facile room temperature solventless synthesis of high thermoelectric performance Ag2Se via a dissociative adsorption reaction. Issue 44 (1st November 2017) - Yang, Dongwang; Su, Xianli; Meng, Fanchen; Wang, Si; Yan, Yonggao; Yang, Jihui; He, Jian; Zhang, Qingjie; Uher, Ctirad; Kanatzidis, Mercouri G.; Tang, Xinfeng
Abstract : The facile room temperature yet solventless synthesis process, characterized by its simplicity, speed, low energy demand, low cost, opens a new avenue for the preparation of high quality silver chalcogenide samples. Abstract : Simultaneous control of the stoichiometry, microstructure, and compositional homogeneity is a prerequisite for understanding the properties of Ag2 Se. These are difficult to attain because of the highly mobile Ag + ions above the superionic phase transition at 407 K. Here we report on a novel synthesis of well crystallized orthorhombic Ag2 Se carried out at room temperature, which requires no expensive instrumentation, and yields a single-phase material in a very short time. Our facile reaction process is a self-sustaining room temperature synthesis driven by the dissociative adsorption of Se by Ag and promoted by stirring and intermittent grinding under ambient conditions. Systematic experimental and theoretical studies of chemical reactions between Ag and Q (Te, Se, and S) revealed that the reaction mechanism between Ag and Q is in line with the Hard Soft Acid Base (HSAB) scheme (rate order Ag2 Te > Ag2 Se > Ag2 S). The low carrier concentration achieved ∼10 18 cm −3 and the optimized weighted majority-to-minority carrier mobility ratio observed in the samples as corroborated by the state-of-the-art thermoelectric performance of ZT ∼1.2 at 390 K attest to the superiority of the synthesis route in yielding highly stoichiometric Ag2 Se samples.